1996
DOI: 10.1111/j.1432-1033.1996.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Multidrug‐Resistance Protein (MRP) as the Glutathione‐S‐Conjugate Export Pump of Erythrocytes

Abstract: The identification of the multidrug resistance protein (MRP) as a conjugate export pump in several cell types suggested its involvement in the long-known glutathione-S-conjugate transport across erythrocyte membranes. We investigated the ATP-dependent transport of glutathione S-conjugates in human erythrocyte and erythroleukemia cell membrane vesicles using the endogenous conjugate leukotriene C, (LTC,), known to be a high-affinity substrate for MRP, in addition to S-(2,4-dinitrophenyl)glutathione. The kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 33 publications
5
48
1
Order By: Relevance
“…Like ABCA1 and ABCB1, ABCB4 may be involved in lipid efflux rather than in the maintenance of plasma membrane lipid asymmetry. ABCC1 (MRP1) was identified initially as a conjugated glutathione transporter (131,132). This enzyme was also shown to catalyze the efflux of short-chain NBD phospholipid analogs, but not endogenous lipids (such as PS), from the inner to the outer monolayer of the erythrocyte (57,133,134) and may account for the previously described efflux activity of these lipids (67,112).…”
Section: Floppasesmentioning
confidence: 99%
“…Like ABCA1 and ABCB1, ABCB4 may be involved in lipid efflux rather than in the maintenance of plasma membrane lipid asymmetry. ABCC1 (MRP1) was identified initially as a conjugated glutathione transporter (131,132). This enzyme was also shown to catalyze the efflux of short-chain NBD phospholipid analogs, but not endogenous lipids (such as PS), from the inner to the outer monolayer of the erythrocyte (57,133,134) and may account for the previously described efflux activity of these lipids (67,112).…”
Section: Floppasesmentioning
confidence: 99%
“…MK571 has been used extensively as an inhibitor of ABCC2, e.g. (Pulaski et al, 1996), and cyclosporin is also an inhibitor (Wortelboer et al, 2003). We used a combination of quercetin conjugates and inhibitors to test interaction with ABCC2 and to assess the predictive power of an in silico generated 3D model of ABCC2.…”
mentioning
confidence: 99%
“…Human erythrocytes were previously demonstrated to constitute a good model to study the transport activity of MRP1 [33,39,[44][45][46]. In this study, we showed that the flavones apigenin and acacetin and the flavonols morin and myricetin were effective inhibitors of MRP1-mediated BCECF efflux from human erythrocytes and also from the MRP1-expressing resistant cancer cell line MDA-MB-231.…”
Section: Discussionmentioning
confidence: 56%
“…The expression of MRP1 [39], MRP4 [40] and MRP5 [41] has thusfar been demonstrated for this cell type. Western blot analysis of erythrocyte membrane preparations performed by Rychlik et al [33] revealed a much higher expression of MRP1 than MRP5, and no P-glycoprotein was recorded in erythrocytes.…”
Section: Modulation Of Mrp1 Transport Activity In Human Erythrocytesmentioning
confidence: 99%